Human MAIT and CD8αα cells develop from a pool of type-17 precommitted CD8 + T cells - Walker, L; Kang, Y; Smith, M; Tharmalingham, H; Ramamurthy, N; Fleming, V; Sahgal, N; Leslie, A; Oo, Y; Geremia, A; Scriba, T; Hanekom, W; et al. (2012)
Human mucosal associated invariant T (MAIT) CD8 + and Tc17 cells are important tissue-homing cell populations, characterized by high expression of CD161 ( ++) and type-17 differentiation, but their origins and relationships remain poorly defined. By transcriptional and functional analyses, we demonstrate that a pool of polyclonal, precommitted type-17CD161 ++CD8αβ + T cells exist in cord blood, from which a prominent MAIT cell(TCR Vα7.2 +) population emerges postnatally. During this expansion, CD8αα T cells appear exclusively within aCD161 ++CD8 +/MAIT subset, sharing cytokine production, chemokine-receptor expression, TCR-usage, and transcriptional profiles with their CD161 ++CD8αβ + counterparts. Our data demonstrate the origin and differentiation pathway of MAIT-cells from a naive type-17 precommitted CD161 ++CD8 +T-cell pool and the distinct phenotype and function of CD8αα cells in man. © 2012 by The American Society of Hematology.